Alignment capabilities of big data's value creation in the context of service delivery processes. Issue 3 (14th December 2020) - Brinch, Morten; Stentoft, Jan; Näslund, Dag
Abstract : Purpose: While big data creates business value, knowledge on how value is created remains limited and research is needed to discover big data's value mechanism. The purpose of this paper is to explore value creation capabilities of big data through an alignment perspective. Design/methodology/approach: The paper is based on a single case study of a service division of a large Danish wind turbine generator manufacturer based on 18 semi-structured interviews. Findings: A strategic alignment framework comprising human, information technology, organization, performance, process and strategic practices are used as a basis to identify 15 types of alignment capabilities and their inter-dependent variables fostering the value creation of big data. The alignment framework is accompanied by seven propositions to obtain alignment of big data in service processes. Research limitations/implications: The study demonstrates empirical anchoring of how alignment capabilities affect a company's ability to create value from big data as identified in a service supply chain. Practical implications: Service supply chains and big data are complex matters. Therefore, understanding how alignment affects a company's ability to create value of big data may help the company to overcome challenges of big data. Originality/value: The study demonstrates how value from big data can be created following an alignment logic. By this, both critical and complementary alignment capabilities have been identified.